Crystal structures of three 3,4,5-trimethoxybenzamide-based derivatives - Gomes, Ligia R. (2016)
The crystal structures of three benzamide derivatives, viz. N-(6-hy-droxy-hex-yl)-3,4,5-tri-meth-oxy-benzamide, C16H25NO5, (1), N-(6-anilinohex-yl)-3,4,5-tri-meth-oxy-benzamide, C22H30N2O4, (2), and N-(6,6-di-eth-oxy-hex-yl)-3,4,5-tri-meth-oxy-benzamide, C20H33NO6, (3), are described. These compounds differ only in the substituent at the end of the hexyl chain and the nature of these substituents determines the differences in hydrogen bonding between the mol-ecules. In each mol-ecule, the m-meth-oxy substituents are virtually coplanar with the benzyl ring, while the p-meth-oxy substituent is almost perpendicular. The carbonyl O atom of the amide rotamer is trans related with the amidic H atom. In each structure, the benzamide N-H donor group and O acceptor atoms link the mol-ecules into C(4) chains. In 1, a terminal -OH group links the mol-ecules into a C(3) chain and the combined effect of the C(4) and C(3) chains is a ribbon made up of screw related R 2 (2)(17) rings in which the ⋯O-H⋯ chain lies in the centre of the ribbon and the tri-meth-oxy-benzyl groups forms the edges. In 2, the combination of the benzamide C(4) chain and the hydrogen bond formed by the terminal N-H group to an O atom of the 4-meth-oxy group link the mol-ecules into a chain of R 2 (2)(17) rings. In 3, the mol-ecules are linked only by C(4) chains.